Sixteen Cowries : Yoruba Divination from Africa to the New World - Bascom, William Russell, 1912-1981 (Book collections on Project MUSE., 1980)
"" ... a landmark in research of African oral traditions.""--African Arts "" ... a significant contribution to the understanding of Yoruba religious belief, magic, and art.""--Journal of Religion in Africa Yoruba texts and English translations of a divination system that originated in Nigeria and is widely practiced today by male and female diviners in the diaspora. A landmark edition